Handbook of toxicologic pathology - Haschek, Wanda M.; Rousseaux, Colin George, 1954-; Wallig, Matthew A. (Academic Press, 2002)
A comprehensive understanding of toxicologic pathology is essential for those in industry, academia, and government who make decisions concerning the safety and efficacy of drugs and chemicals. Toxicologic Pathology relies heavily on the fields of both toxicology and pathology, which are well covered individually in various texts and references; however, there are few texts that address the field of toxicologic pathology. The Handbook of Toxicology Pathology fills this void and is thus essential for all health professionals within or interacting with the field of toxicologic pathology. This two-volume set provides the reader with a single reference for toxicologic pathology. In volume I, the book covers toxicologic pathology in its basic aspects, including its definition, the basic biochemical and morphologic mechanisms underlying the discipline, the basic practice of toxicologic pathology (including special techniques) and issues essential to the understanding of toxicologic pathology such as risk assessment, experimental design, and statistical analysis. Next, the book moves to specific issues affecting the "practice" toxicologic pathology, including issues such as knowledge management, regulatory affairs and writing pathology reports. Finally, Volume I closes with several chapters that deal with specific classes of environmental toxicants such as endocrine disruptors and heavy metals. Volume II addresses the toxicologic pathology in a thoroughly standardized systems manner, addressing the basic structure and function of a particular organ system, its response to toxic injury, mechanisms of injury and methods of evaluation of such injury. Key Features * Easy to find, up-to-date reference information * Graphic and photographic plates * Current hot topics and anticipated changes in toxicologic pathology * Standardized chapter format * Topics that are addressed in both a broad and deep manner, resulting in a stand alone text * Added coverage of important environmental toxicants * Chapters authored by internationally recognized experts and peer-reviewed